RESULTS OF EMERGENCY MANAGEMENT OF UPPER GASTROINTESTINAL BLEEDING DUE TO RUPTURED ESOPHAGEAL VARICES AT NGHE AN FRIENDSHIP GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics and treatment outcomes of emergency management in patients with upper gastrointestinal bleeding due to ruptured esophageal varices at Nghe An Friendship General Hospital.Subjects and methods: This study describes a prospective study of 74 patients admitted to the Emergency Department from December 2024 to June 2025.  Results: 81.1% of patients were discharged, 18.9% requested to be discharged due to severe conditions, 93.3% of patients had their bleeding source controlled, and 16.3% experienced a first recurrence of bleeding.Conclusion: Gastrointestinal bleeding due to ruptured varices primarily affects men, with alcohol being the leading cause. Patients require early diagnosis and control of the bleeding source, as well as treatment of other complications of cirrhosis such as hepatic encephalopathy and hepatorenal syndrome. Diagnosis and treatment require multidisciplinary collaboration to achieve maximum effectiveness.
Keywords: Gastrointestinal bleeding due to esophageal varices